2013
DOI: 10.1093/jxb/ert138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon to nitrogen ratios on soybean somatic embryo (cv. Jack) growth and composition

Abstract: Soybean [Glycine max (L.) Merr.] seed are valued for their protein and oil content. Soybean somatic embryos cultured in Soybean Histodifferentiation and Maturation (SHaM) medium were examined for their suitability as a model system for developing an understanding of assimilate partitioning and metabolic control points for protein and oil biosynthesis in soybean seed. This report describes the growth dynamics and compositional changes of SHaM embryos in response to change in the carbon to nitrogen ratio of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…The concept of C and N limitations to oil and protein yield formation is based on reported findings in embryo culture (Truong et al, 2013) and helps contextualize the results of these source-sink treatments. The concept of C and N limitations to oil and protein yield formation is based on reported findings in embryo culture (Truong et al, 2013) and helps contextualize the results of these source-sink treatments.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of C and N limitations to oil and protein yield formation is based on reported findings in embryo culture (Truong et al, 2013) and helps contextualize the results of these source-sink treatments. The concept of C and N limitations to oil and protein yield formation is based on reported findings in embryo culture (Truong et al, 2013) and helps contextualize the results of these source-sink treatments.…”
Section: Data Collectionmentioning
confidence: 99%
“…In other words, a reduced C/N ratio available to the developing seed under shade likely resulted in an increased seed protein concentration indirectly through reduced oil concentration. The concept of C and N limitations to oil and protein yield formation is based on reported findings in embryo culture (Truong et al, 2013) and helps contextualize the results of these source-sink treatments. Additionally, research on highprotein genotypes has shown that these lines yield less than normal protein lines (Serretti et al, 1994; due to reduced seed set, which afforded greater N reserves per seed.…”
Section: Data Collectionmentioning
confidence: 99%
“…In developing seeds or cell-culture suspensions metabolism operates at a pseudo steady state during periods of development, therefore isotopically labeling these tissues with a mixture of labeled and unlabeled substrates will result in redistribution of the isotope that reflects pathway use and flux. Such studies have been regularly performed with metabolic flux analysis to document the partitioning of carbon, energy and reducing equivalents to oil, protein and carbohydrate in seeds or cell cultures [57][58][59][60][61][62][63][64]. However steady state labeling analyses are limited to assessments of pathways that enzymatically rearrange the distribution of isotope.…”
Section: Steady State and Transient Labelingmentioning
confidence: 99%
“…At the biochemical level these studies have provided insight to wild-type metabolic operation as well as the response to genetic or environmental conditions. By changing the temperature [226], oxygen [62,227] nutrient status [57,61,63,64,228] or through genetic manipulation of central metabolism [59,229,230], or lipid metabolism [120] plant cells are forced to rebalance resource utilization resulting in altered phenotypes.…”
Section: Assessing Resource Partitioning Through Perturbation-responsmentioning
confidence: 99%
“…***Significant at the P ≤0.001. Starch and protein biosynthesis depend on the carbon to nitrogen ratio (C:N) and have shown positive and negative correlations with C:N, respectively (Truong et al, 2013). ‡ ns, not significant.…”
Section: Discussionmentioning
confidence: 99%